La oralidad como estrategia estimuladora del lenguaje en niños de 5 años de la Unidad Educativa “ANA PÁEZ” de la ciudad de Latacunga en el período lectivo 2022 -2023. - Chanatásig Chasiquiza, Lourdes Margoth (2023)
The development of language affects the achievement of words to be able to express oneself (vocabulary); Unfortunately, the educational processes have not been adequately directed, due to the long time that the children remained isolated due to the pandemic; therefore, the learning processes have not been adequately developed, the Ana Páez Educational Unit of the Eloy Alfaro parish, Latacunga canton has not been the exception and a high deficit in language development has been observed in the students since they have not received stimuli from home due to various factors, this impairs the development of orality. It is therefore necessary to analytically review the curricular activities for the achievement of significant learning taking into account what children need to develop and learn from the educational center and the family.